2019
DOI: 10.2807/1560-7917.es.2019.24.25.1900053
|View full text |Cite
|
Sign up to set email alerts
|

Population perception of mandatory childhood vaccination programme before its implementation, France, 2017

Abstract: Background Vaccination policy in France was previously characterised by the coexistence of eight recommended and three mandatory vaccinations for children younger than 2 years old. These 11 vaccines are now mandatory for all children born after 1 January 2018. Aim To study the French population’s opinion about this new policy and to assess factors associated with a positive opinion during this changing phase. Methods A cross-sectional survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 30 publications
6
26
0
Order By: Relevance
“…Our findings indicate that around 90,000 incident symptomatic infections, corresponding to 9 out 10 cases, were not ascertained by the surveillance system in the first 7 weeks following lockdown from May 11 to June 28 2020, although the test positivity rate did not exceed WHO recommendations (5%) 5 . The median detection rate increased from 7% [6-8]% to 38% [35][36][37][38][39][40][41][42][43][44]% over time, with large regional variations, owing to a strengthening of the system as well as a decrease of epidemic activity. According to participatory surveillance data, only 31% of individuals with COVID-19-like symptoms consulted a doctor in the study period.…”
mentioning
confidence: 99%
“…Our findings indicate that around 90,000 incident symptomatic infections, corresponding to 9 out 10 cases, were not ascertained by the surveillance system in the first 7 weeks following lockdown from May 11 to June 28 2020, although the test positivity rate did not exceed WHO recommendations (5%) 5 . The median detection rate increased from 7% [6-8]% to 38% [35][36][37][38][39][40][41][42][43][44]% over time, with large regional variations, owing to a strengthening of the system as well as a decrease of epidemic activity. According to participatory surveillance data, only 31% of individuals with COVID-19-like symptoms consulted a doctor in the study period.…”
mentioning
confidence: 99%
“…Mandatory vaccination can raise conflicting issues on a parent's right to choose what they consider is in the best interest of their child. Effects of exercising these rights which should be discussed included the fact that the development of herd immunity in the community is threatened and children cannot be protected against serious and preventable diseases [44][45][46]. Some HCWs recommended the assessment of vaccination cards and implementation of some limitations in school enrollment for children with incomplete vaccination;…”
Section: Initiatives Relating To Familiesmentioning
confidence: 99%
“…On one hand, someone argues that compulsory vaccination diminishes autonomy for parents making decisions on behalf of their children, but at the same time mandates ensure greater equity, and that without them some people would receive the indirect benefits of vaccination without the even small risks related to it [21]. Moreover, there are studies disproving that the implementation of compulsory vaccination may lead to opposing attitudes and/or have other negative effects [22], and a survey conducted in France before the implementation of the law showed that two-thirds of the participants agreed with the extension of the vaccine mandates [23]. Although detrimental effects consisting of refusing the uptake of non-mandatory vaccines by individuals with rather negative attitudes toward vaccines previously exposed to mandatory vaccinations have been reported in experimental studies [24], they are not necessarily observed in the real world.…”
Section: Europe On the Movementioning
confidence: 99%